Primary vulvovaginal paraganglioma. Case report - Reyna-Villasmil, Eduardo (2019)
Paraganglioma is an extra-adrenal neuroendocrine neoplasia derived from neural crest precursors that arise in association with autonomic ganglia. Also called extraadrenal pheochromocytomas, these tumors are defined by their anatomical site and whether they are hormonally functional. Paragangliomas are rare neoplasms of the female genital tract and may be located in the ovaries, uterus or cervix. Those that appear in the vulvovaginal region are extremely rare. Clinical manifestations depend on unregulated catecholamine secretion and location. Diagnosis is based on morphological and immunohistochemical findings. Surgical resection is the primary treatment for this tumor as it does not respond to chemotherapy and radiotherapy. Due to its low frequency and nonspecific symptomatology, diagnosis may be difficult. We present a case of primary vulvovaginal paraganglioma.